Light absorption enhancement in thin film GaAs solar cells using dielectric nanoparticles - Fateh A. Chaudhry; Lorena Escandell; Eduardo López-Fraguas; Ricardo Vergaz; José Manuel Sánchez-Pena; Braulio García-Cámara (Scientific Reports, 2022)
Abstract Cost-effective and lightweight solar cells are currently demanded in strategic fields such as space applications or integrated-wearable devices. A reduction of the active layer thickness, producing thin-film devices, has been a traditional solution to accomplish both requirements. However, this solution also reduces the efficiency of the device. For this reason, alternative strategies are being proposed. In this work, light trapping effects of an array of semiconductor nanoparticles located on the top surface of a thin-film GaAs solar cell are investigated to improve the optical absorption and current density in active layer, under the standard AM-1.5 solar spectrum. The numerical results are compared with other previous proposals such as an aluminum nanoparticle array, as well as conventional solar cells with and without a standard anti-reflective coating (ARC). The inclusion of semiconductor nanoparticles (NPs) shows an improved response of the solar cells at different angles of incidence in comparison to solar cell with an ARC. Furthermore, the efficiency increases a 10% respect to the aluminum nanoparticles (NPs) architecture, and a 21% and a 30% respect to solar cells with and without ARC, respectively.